Does the Delivery System Matter? The Scaling-Out of a School-Based Resilience Curriculum to the Social Services Sector - Lilja, Josefine L.; Kimber, Birgitta; Eriksson, Charli; Henriksson, Barbro; Skoog, Therése (Frontiers in Psychiatry, 2021)
Background: The context is highly relevant to the implementation of new health-related programs and is therefore an implicit or explicit part of the major implementation models in the literature. The Resilience Curriculum (RESCUR) program was developed to foster the psychosocial development of children in early and primary education. This study aimed to examine the scaling-out of RESCUR, specifically to test if the quality of implementation of RESCUR differs between the school and social services sectors. Methods: RESCUR was implemented in schools and social services in Sweden 2017–2019. Data were collected via leaders’ self-reports and observation protocols at three months after the implementation started. There were 34 self-reports collected from schools, and 12 from the social services sector; 30 observation protocols were collected from schools and 10 from social services. The data analysis examined if there were differences in the implementation quality of RESCUR (in, e.g., dosage, duration, fidelity, adaptation, quality of delivery) between the two delivery systems Results: Analyses of both the observation protocols and leaders’ self-reports revealed that RESCUR was implemented with high quality in both schools and social services. The results showed a few significant differences in the quality of implementation between the sectors, including with regard to dosage and duration. Conclusions: Overall, the findings suggest that the resilience program designed for delivery in schools can be scaled-out to social services with sustained implementation quality. Future research is needed to test the effectiveness of the program on child health-related outcomes.